Simple combination method of FTIR spectroscopy and chemometrics for qualitative identification of cattle bones. (November 2019) - Nadia, Y; Ramli, M; Muslem; Japnur, A F; Rusyana, A; Idroes, G M; Suhendra, R; Muhammad; Sasmita, N R; Tallei, T E; Idroes, R
Abstract: This research aims to identify Aceh, Bali and Brahman cattle bones using Fourier-Transform Infrared (FTIR) spectroscopy combined with chemometrics through Principal Component Analysis (PCA). Cattle bone samples were obtained from Lambaro and Lampulo raditional market in Aceh Besar. Firstly, each bone sample was analyzed using FTIR and then followed by FTIR spectra analysis using PCA. FTIR spectra showed that inorganic samples produced from these cattle bones consisting of hydroxyl, carbonate and phosphate functional groups. Further inspection using the PCA plot, the cattle bones were separated into three groups with its difference of 90.03%. Three types of cattle bone (Aceh, Bali dan Brahman) are separated into different quadrants. Inspite of both Aceh cattle data are closed each to others and are located in the same quadrant. This experiment proved that the cattle bones of Aceh, Bali dan Brahman can be well distinguished by using the combination method of FTIR and PCA.